Transformerless high gain boost converter for low power applications with feedback control - Md Yaseen; dr. P Usha (Institute of Advanced Engineering and Science, 2015)
A transformer-less boost converter which provides high voltage gain without utilizing transformer or coupled inductors and extreme duty cycle is proposed in this paper. Also it is able to cancel the ripples in the input current at a preselected duty cycle, without increasing the number of components. The converter combines the features of boost converter and a three switch high voltage converter. At the input side, two inductors are interleaved for cancelling the input current ripple and at the output side switched capacitor voltage multiplier is used to increase the voltage gain. Feedback control is used to make the output voltage constant in spite of variation in the input or load or both i.e. both line and load regulation is accompanied. This proposed converter configuration helps eliminate the input current ripple and provides voltage deregulation for low power applications.